LIMITED EVIDENCE ON IMAGING FOR DETECTING PROSTATE CANCER: A SYSTEMATIC REVIEW - Abdulloh, Arizal (Transpublika Publisher, 2022)
This research aims to assess the diagnostic accuracy of imaging technology in detecting prostate cancer in patients with high PSA levels or suspicious findings in clinical examinations. The method involved searching for articles from the Medline, EMBASE, and Cochrane databases from 2011 to 2023. The selected articles used predefined inclusion criteria, and the risk of bias in individual studies was assessed using QUADAS-2. The abstracts and full texts were independently evaluated by the authors to assess the sensitivity and specificity of the imaging. The selection process followed the PRISMA 2020 guidelines. The literature search yielded 5421 abstracts, which were independently reviewed by the authors. Out of this number, 5401 abstracts were excluded due to irrelevance to the research title and abstract. Subsequently, a full review was conducted on 20 articles to assess their quality. Among the 20 articles, 14 studies were excluded because they were not original research, the PICO was not relevant, or the methods and populations used were not adequately described. Finally, six studies were included in this research, with four studies concerning MRI and two studies involving transrectal ultrasound with Doppler. Overall, the research findings indicate that the current number of imaging studies with adequate scientific quality is still limited to recommend their use beyond clinical trials for patients with high PSA levels or suspicious findings in clinical examinations. Therefore, further research is needed to strengthen and generalize these findings before imaging technology can be widely used as a diagnostic method for prostate cancer in this patient group.